Microcontroller base full bridge forward power supply unit - Muhamad Azizan, Mat Sirat (2008)
Nowadays, there are many power supply unit topologies. In this project, it is been proposed to do the full-bridge dc-dc converter topology. The full-bridge c dc-dc converter topology was chosen for several reasons. The primary benefit of using a Full-Bridge dc-dc converter is its power handling capabilities, stability, and symmetry. Secondly, using a high frequency transformer is one of the most efficient ways to step up or step down the voltage and to transfer the power to the full-wave rectifier circuit. Basically, this topology is referred to the use of switch mode power supply (SMPS) technique. In designing SMPS, it used high frequency transformer. The purpose of a power transformer in Switch-Mode Power Supplies is to transfer power efficiently and instantaneously from an external electrical source to an external load. In doing so, the transformer also provides important additional capabilities. As mentioned just now, this design uses the high frequency switch. Therefore, a controller is needed to control or vary the duty cycle of PWM during switching time. In this design, PIC is chosen as the main controller of this PSU. PIC was chosen because of ease to program the switching time of four switches. Normally, MOSFET or IGBT is selected for the power switch. Circuit driver is also needed to drive voltage signal from PIC to the power switches. In this case, suitable IC driver must be used.